2014
DOI: 10.1002/jsfa.6650
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the dietary incorporation of olive leaves on growth performance, digestibility, blood parameters and meat quality of growing pigs

Abstract: The data indicate that olive leaves may be included in pig diets at 25 g kg(-1) in order to improve the tocopherol content of meat without excessively compromising growth performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 23 publications
0
17
1
1
Order By: Relevance
“…These values were slightly higher than that (14.4; 17.4 kg and 37.4 g/day, respectively, for initial, final weight and ADG) registered by Bunyeth and Preston () for goats receiving grass hay. In other study, Paiva‐Martins et al () showed that the incorporation of olive leaves (OL) in the feeding of pigs significantly decreased growth performance ( p = .010) and backfat thickness ( p = .035) and increased feed/gain ratio ( p = .032). Likewise, pigs fed diets with olive leaves had lower daily weight gain and daily feed intake than pigs fed a conventional diet (Paiva‐Martins et al ).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…These values were slightly higher than that (14.4; 17.4 kg and 37.4 g/day, respectively, for initial, final weight and ADG) registered by Bunyeth and Preston () for goats receiving grass hay. In other study, Paiva‐Martins et al () showed that the incorporation of olive leaves (OL) in the feeding of pigs significantly decreased growth performance ( p = .010) and backfat thickness ( p = .035) and increased feed/gain ratio ( p = .032). Likewise, pigs fed diets with olive leaves had lower daily weight gain and daily feed intake than pigs fed a conventional diet (Paiva‐Martins et al ).…”
Section: Discussionmentioning
confidence: 95%
“…These values were slightly higher than that (14.4; 17.4 kg and 37.4 g/day, respectively, for initial, final weight and ADG) registered by Bunyeth and Preston (2006) for goats receiving grass hay. In other study, Paiva-Martins et al (2014) showed that the incorporation of olive leaves (OL) in the feeding of pigs significantly decreased growth performance (p = .010) and backfat thickness (p = .035) and increased feed/gain ratio (p = .032 However, the low ADG for all animals might be due to the age of kids (≥4 months in the beginning of the experiment). In fact, Najari (2005) reported that the age of the maximum growth rate for indigenous Tunisian goat's kids ranged between 35 and 45 days when the mean ADG was 102 g/day; the growth rate decreased progressively and becomes lower than 30 g/day after the age of 5 months.…”
Section: Feed Intake and Growth Performancementioning
confidence: 95%
“…Moreover, olive leaves rich in oil cause a decrease of ruminal protozoa leading to an increase in the efficiency of microbial protein synthesis in the rumen (Molina-Alcaide and Yanez-Ruiz, 2008 in milk fat quality compared to diets based on conventional forages (Molina-Alcaide and Yanez-Ruiz, 2008). Therefore, olive leaves could be considered as an important raw-material that have the potential to be used as a natural antioxidant and as an ingredient for the stabilization of vegetable oil (Keceli and Harp, 2014) and animal feed (Molina-Alcaide and Yanez-Ruiz, 2008;Botsoglou et al, 2014;Paiva-Martins et al, 2014), but it is important to mention that they could also be used to improve human health (Anter et al, 2011).…”
Section: Introductionmentioning
confidence: 98%
“…As substâncias ativas das plantas são capazes de alterar a estrutura fosfolipídica da membrana celular, interrompendo o sistema enzimático, comprometendo o material genético da bactéria e formando compostos tóxicos, como o peróxido de hidrogênio (AFONSO, 2014;CIRQUEIRA, 2010). A ação positiva das folhas de oliveira in vivo também foi verificada em filés de peru e em carne suína (PAIVA-MARTINS et al, 2013;BOTSOGLOU et al, 2012;PAIVA-MARTINS et al, 2009) e, em todas as pesquisas, o efeito positivo diante das bactérias foi atribuído à presença de compostos fenólicos e à oleuropeína, o que, conforme mencionado por , recomenda o uso de folhas de oliveira como suplemento nutricional ou componente funcional de alimentos, ou Gökmen et al (2014) que indicam o uso de folhas de oliveira pela indústria de alimentos como um antimicrobiano natural.…”
Section: Marangoni C Et Alunclassified